The economic and social impact of Thailand's rural job creation programs - Krongkaew, Medhi (Philippine Review of Economics and Business (formerly The Philippine Review of Business and Economics), 1987)
The subject of this paper is the description and analysis of the Rural Job Creation Program (RJCP), a novel approach which was adopted by the Thai government to supplement its rural development policies. The paper first traces the origin of this unique concept of development policy. It then discusses five aspects of the structure and implementation of the RJCP, namely its objectives, administrative structure, project preparation and implementation procedures, financial control, and its monitoring and evaluation. It then details the economic impact of RJCP in terms of income as well as employment generation. It also discusses some of the results of evaluation surveys on whether the RJCP helped in developing efficiency in local self-government as well as in increasing local level participation in rural development efforts.